The scope of equal access to public office and its judicial guarantees - Saeed, Hawraman Muhammad; Muhammad, Hana Nasser (Journal of Legal and Political Studies, 2022)
The principle of equality in access to public office is one of the most scientific principles in the functional field، as it is the first forms to ensure that all citizens enjoy their right to public office on an equal footing. In order to establish the principle of equality in the job، the legislator has imposed a set of preconditions for joining the advertised job، by setting conditions and imposing methods for the selection of the best and repair of human resources capable of bearing the responsibilities of this job، and its violation may result in the invalidity of joining it، under penalty of judicial guarantees devoted to the protection of the principle of equality in the job.
Keywords: principle of equality in access to public office; citizens; principle of equality in the job; judicial guarantees; violation